Development of an Italian RM Y-STR haplotype database: Results of the 2013 GEFI collaborative exercise. (March 2015) - Robino, C.; Ralf, A.; Pasino, S.; De Marchi, M.R.; Ballantyne, K.N.; Barbaro, A.; Bini, C.; Carnevali, E.; Casarino, L.; Di Gaetano, C.; Fabbri, M.; Ferri, G.; et al.
Abstract: Recently introduced rapidly mutating Y-chromosomal short tandem repeat (RM Y-STR) loci, displaying a multiple-fold higher mutation rate relative to any other Y-STRs, including those conventionally used in forensic casework, have been demonstrated to improve the resolution of male lineage differentiation and to allow male relative separation usually impossible with standard Y-STRs. However, large and geographically-detailed frequency haplotype databases are required to estimate the statistical weight of RM Y-STR haplotype matches if observed in forensic casework. With this in mind, the Italian Working Group (GEFI) of the International Society for Forensic Genetics launched a collaborative exercise aimed at generating an Italian quality controlled forensic RM Y-STR haplotype database. Overall 1509 male individuals from 13 regional populations covering northern, central and southern areas of the Italian peninsula plus Sicily were collected, including both "rural" and "urban" samples classified according to population density in the sampling area. A subset of individuals was additionally genotyped for Y-STR loci included in the Yfiler and PowerPlex Y23 (PPY23) systems (75% and 62%, respectively), allowing the comparison of RM and conventional Y-STRs. Considering the whole set of 13 RM Y-STRs, 1501 unique haplotypes were observed among the 1509 sampled Italian men with a haplotype diversity of 0.999996, largely superior to Yfiler and PPY23 with 0.999914 and 0.999950, respectively. AMOVA indicated that 99.996% of the haplotype variation was within populations, confirming that genetic-geographic structure is almost undetected by RM Y-STRs. Haplotype sharing among regional Italian populations was not observed at all with the complete set of 13 RM Y-STRs. Haplotype sharing within Italian populations was very rare (0.27% non-unique haplotypes), and lower in urban (0.22%) than rural (0.29%) areas. Additionally, 422 father-son pairs were investigated, and 20.1% of them could be discriminated by the whole set of 13 RM Y-STRs, which was very close to the theoretically expected estimate of 19.5% given the mutation rates of the markers used. Results obtained from a high-coverage Italian haplotype dataset confirm on the regional scale the exceptional ability of RM Y-STRs to resolve male lineages previously observed globally, and attest the unsurpassed value of RM Y-STRs for male-relative differentiation purposes.